WHAT HAPPENS TO CELLULOSIC FIBERS DURING PAPERMAKING AND RECYCLING? A REVIEW - Orlando J. Rojas; Richard A. Venditti; Martin A. Hubbe (BioResources, 2007)
Both reversible and irreversible changes take place as cellulosic fibers are manufactured into paper products one or more times. This review considers both physical and chemical changes. It is proposed that by understanding these changes one can make better use of cellulosic fibers at various stages of their life cycles, achieving a broad range of paper performance characteristics. Some of the changes that occur as a result of recycling are inherent to the fibers themselves. Other changes may result from the presence of various contaminants associated with the fibers as a result of manufacturing processes and uses. The former category includes an expected loss of swelling ability and decreased wet-flexibility, especially after kraft fibers are dried. The latter category includes effects of inks, de-inking agents, stickies, and additives used during previous cycles of papermaking.